LANGUAGE FUNCTION IN KFC ADVERTISEMENT’S VIDEO - Astari, Dewa Ayu Berlian Trinanda (ID Solutions, 2023)
This study aimed to analyse the type oflanguage functions communicated in KFCadvertisements video, as well as the sentence types used to convey those language functions. A descriptive qualitative method was performed on the data todescribe the language functions and sentence types. The study also used of a quantitative method to highlight and illustrate the occurrences of language function types and sentence types. The data was collected through observation method. This investigation used two theories to achieve its objectives. Theory by Jakobson (1980) used to analysed the types of language function, contrasted with the theory by Quirk and Greenbaum's (1990) which was used to analysis of the sentence types employed to present those language functions. As the result, the KFCadvertisements video had 31 utterances contained language functions in KFC advertisements video. There were referential functions, emotive functions, conative functions, phatic functions, metalingual functions, and poetic functions.